Approaches to the study of progress, monitoring of sports training and selection of athletes in a sports context - Guba V.P. ,; Levushkin S.P. ,; Lyakh V.I. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to systematise the research of domestic specialists on the development, control of physical abilities and their assessment in the selection process. Methods and structure of the study. An analysis of literature and online sources was conducted, along with a logical comparison of the available material and reports from scientific and practical conferences by leading scientists in the field of sports training and morphofunctional diagnostics. Results and conclusions. This article attempts to propose a research framework for studying the effectiveness of various aspects of athlete preparedness. It outlines the main aspects of a basic system of interdisciplinary research in the field of sport, carried out by Russian scientists with highly effective end results.